Altorientalische Studien zu Ehren von Pascal Attinger: mu-ni u4 ul-li2-a-aš ĝa2-ĝa2-de3 - Mittermayer, Catherine; Ecklin, Sabine; Attinger, Pascal (Orbis biblicus et orientalis, 2012)
Bibliogr. P. Attinger S. [XIII] - XVII. - Literaturangaben